Time-frequency catalogue: JSON implementation and python library - Cecconi, Baptiste; Louis, Corentin K.; Bonnin, Xavier; Loh, Alan; Taylor, Mark B. (Frontiers in Astronomy and Space Sciences, 2023)
TFCat (Time-Frequency Catalogue) is a data interchange format based on JSON, which has been initially designed for exchanging low frequency radio events and features. It defines several types of JSON objects and the manner in which they are combined to represent data about time-frequency features of a time spectrogram (a.k.a., dynamic spectrum), their properties, and their temporal and spectral extents. This implementation is inheriting from the GeoJSON file format. The TFCat python library is implementing this specification and provides a software interface permitting to create, update and validate TFCat objects efficiently. A TFCat object validator is also available.